1995
DOI: 10.1111/j.1528-1157.1995.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impairments of Spatial Memory and Social Behavior in Two Models of Limbic Epilepsy

Abstract: To explore memory impairments in temporal lobe epilepsy, we used two experimental models in the rats: (a) kainate-induced status epilepticus (SE) resulting in excitotoxic damage and in later spontaneous seizures; and (b) amygdala kindling, known to induce no lesions (or only minor) and neuronal reorganization. Long-term effects of these models on memory were investigated with a spatial learning task in a radial-arm maze, and a social interaction test that implies degree of short-term memory. An histological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 48 publications
4
20
0
1
Order By: Relevance
“…Li-Pilo SE is known to impair spatial memory (Detour et al, 2005). Spatial memory was also diminished in KA or pentylenetetrazole-induced SE models (Letty et al, 1995;Mortazavi et al, 2005). Our SE group was severely impaired in the spatial learning task, as shown by the time to reach learning criterion and number of memory errors.…”
Section: Discussionmentioning
confidence: 60%
“…Li-Pilo SE is known to impair spatial memory (Detour et al, 2005). Spatial memory was also diminished in KA or pentylenetetrazole-induced SE models (Letty et al, 1995;Mortazavi et al, 2005). Our SE group was severely impaired in the spatial learning task, as shown by the time to reach learning criterion and number of memory errors.…”
Section: Discussionmentioning
confidence: 60%
“…The early phase after the initial precipitating injury (IPI) such as status epilepticus (SE) or hippocampal injury is characterized by an increased DG neurogenesis and abnormal migration of a substantial fraction of newly generated granule cells into the dentate hilus (Gray and Sundstrom, 1998; Parent et al, 1997, 2006; Scharfman et al, 2000, 2002, 2003; Gong et al, 2007; Scharfman and Gray, 2007; Kuruba et al, 2009). In contrast, the chronic phase of TLE exhibits substantially declined DG neurogenesis (Hattiangady et al, 2004; Hattiangady and Shetty, 2008a), and is associated with spontaneous recurrent motor seizures (SRMS), learning and memory impairments and depression (Letty et al, 1995; Schwarcz and Witter, 2002; Rao et al, 2006a, 2007). Because of the perceived functions of DG neurogenesis concerning learning, memory and mood (Shors et al, 2001; van Praag et al, 2002; Drapeau et al, 2003; Santarelli et al, 2003; Aimone et al, 2006; Sahay and Hen, 2007; Dupret et al, 2008; Imayoshi et al, 2008), it is plausible that decreased DG neurogenesis during chronic epilepsy contributes to impairments in these functions.…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, spatial memory of temporal lobe epileptic rats is shown to be compromised (5,6). Light-discrimination tasks and Y-maze performance also are impaired in epileptic animals, and CBZ reverses these difficulties (7,8).…”
mentioning
confidence: 99%